Part-Time Wage-Gap in Germany: Evidence across the Wage Distribution - Tõnurist, Piret; Pavlopoulos, Dimitris (Journal of Income Distribution®, 2016)
This article uses insights from labour-market segmentation theory in order to investigate the wage differences between part-time and full-time workers in Germany at different parts of the wage distribution. This is accomplished with the use of a quintile regression and panel data from the German Socio Economic Panel (1991-2012). To obtain insights on the part-time wage differentials, we apply a counterfactual wage decomposition analysis. The results indicate the presence of a part-time wage penalty for involuntary part-time work at the low and middle parts of the wage distribution. In contrast, a wage premium for voluntary part-time work emerges, especially at the top of the distribution. Moreover, at the lower end of the wage distribution, part-time workers receive lower returns for their labour market characteristics, indicating the segmentation of the labour market. In contrast, the difference in the characteristics of part-timers and full-timers fully explains the part-time wage gap at the top of the wage distribution.